PUBLIC, FINANCIAL AND MANAGERIAL EFFECTS ON AUTHORITY STYLES IN PUBLIC AND PRIVATE SECTOR: A CASE STUDY IN LIC AND RELIANCE INSURANCE - Gadaboina, Thirupathi (Indian Journal of Finance and Banking, 2022)
Flourishing Authority practices like values, virtues, dispositions, attributes, and competencies improve employee outcomes. Few Authority practices in the form of strategies were selected to achieve better performance. The Authority styles were associated with public, financial, and managerial proportions of employees together in public and private sectors would assist the correlation among Authority styles and proportions disturbing the Authority styles which would be supportive to identify the main important policy variables for recovering the Authority styles. The presentation was based on the primary source of data of the public sector, the LIC, and the private sector; Reliance Insurance was chosen voluntarily for the research because of the researcher's awareness of different regions of Telangana. The data was gathered using the five points Likert scale. The study concluded that authority styles in both sectors managers distinguish the employees under supervision without any wisdom of accountability.JEL Classification Codes: H81, I13, J24, I18.